BAVEL, Bas van; CURTIS, Daniel R.; DIJKMAN, Jessica; HANNAFORD, Matthew; KEYZER, Maïka de; ONACKER, Eline van; SOENS, Tim (2020), Disasters and History: The vulnerability and Resilience of Past Societies, Londres, Cambdrige University Press. ISBN 978-1-108-47717-8, 225 pp. - Lopes, Ana Isabel (História: revista da Faculdade de Letras da Universidade do Porto, 2022)
BAVEL, Bas van; CURTIS, Daniel R.; DIJKMAN, Jessica; HANNAFORD, Matthew; KEYZER, Maïka de; ONACKER, Eline van; SOENS, Tim (2020), Disasters and History: The vulnerability and Resilience of Past Societies, Londres, Cambdrige University Press. ISBN 978-1-108-47717-8, 225 pp.